Mariculture in Kudat and Kota Marudu, Sabah - Wong Hock Tsen; Lee Hock Ann; Rosazman Hussin; Ejria Saleh (Penerbit UMS, 2018)
This study provides a profile of mariculture that is cultivation of mainly grouper in Kudat and Kota Marudu, Sabah using a structured questionnaire and in-depth interview. This study tries to survey all the mariculture operators in grouper cultivation in Kudat and Kota Marudu, Sabah, which altogether are 12 mariculture operators. 11 mariculture operators are surveyed in Kudat whilst there is only one mariculture operator found and surveyed in Kota Marudu. Generally, mariculture in grouper is relatively a medium scale business. The mariculture operators are dominated by the middled age men. The owner of the mariculture operators is mostly Chinese. The majority of them have education only up to the secondary school level. The mariculture operators mostly own their business and learn themselves about mariculture. Mostly, they setting-up their business using their own capital. The mariculture operators acknowledge the importance of environment on their business. Women are mostly important in supporting mariculture business. The mariculture operators mostly conduct mariculture business as sub-business. Mariculture in grouper can be a good business in Kudat and Kota Marudu besides there are several challenges shall be addressed in the business. The government can contribute significantly to the development of the mariculture sector.